Fetal-type gastrointestinal adenocarcinoma: a morphologically distinct entity with unfavourable prognosis. Issue 3 (16th August 2017) - Arora, Kshitij; Bal, Munita; Shih, Angela; Moy, Andrea; Zukerberg, Lawerence; Brown, Ian; Liu, Xiuli; Kelly, Paul; Oliva, Esther; Mullen, John; Ahn, Soomin; Kim, Kyoung-Mee; et al.
Abstract : Aims: This multi-institutional study and a re-evaluation of the TCGA cohort explores the morphological spectrum, genetics and outcome of GI (gastrointestinal) hepatoid tumours, tumours expressing alpha-fetoprotein (AFP) and fetal-type (FT) GI adenocarcinomas. Methods: 44 tumours with evidence of hepatocellular differentiation were evaluated for morphology as well as by immunohistochemistry for AFP, HepPar1, glypican-3 and arginase-1 and by in situ hybridisation for albumin. Three categories were defined: type I (hepatoid: morphological evidence of hepatocellular differentiation), type II (FT GI adenocarcinoma: tubular profiles and subnuclear vacuolisation, resembling fetal intestine) and type III: positive for at least two hepatocyte-specific markers but lacking morphological evidence of hepatocellular differentiation. GI adenocarcinomas in the TCGA cohort were also evaluated (n=829). Results: 18 cases were classified as type I, 19 as FT GI adenocarcinomas and 7 as type III (resembling conventional gastrointestinal carcinomas). Serum AFP was elevated in 92% of cases. 93% of tumours were positive for glypican-3, 90% for albumin and 89% for AFP. Arginase-1 was restricted to 35% of type 1 tumours. TCGA gastric tumours with elevated AFP expression showed morphological features of FT GI adenocarcinoma (70%) and were exclusively MSI stable. TCGA gastric adenocarcinomas with high AFP expression showed inferior survival on univariate and multivariate analysis. Conclusions: FT GI adenocarcinomas show a distinctive morphological and immunohistochemical profile. Gastric adenocarcinomas with elevated expression of AFP morphologically resemble FT GI adenocarcinomas, demonstrate aggressive behaviour, independent of grade and stage, and a distinct genetic profile.